Keratins and lipids in ethnic hair - Cruz, Célia F. (2013)
Human hair has an important and undeniable relevance in society due to its important role in visual appearance and social communication. Hair is mainly composed of structural proteins, mainly keratin and keratin associated proteins, and lipids. Herein, we report a comprehensive study of the content and distribution of the lipids among ethnic hair, African, Asian and Caucasian hair. More interestingly, we also report the study of the interaction between those two main components of hair, specifically the influence of the hair internal lipids in the structure of the hair keratin. This was achieved by the use of a complete set of analytical tools such as thin layer chromatography-flame ionization detector, X-ray analysis, molecular dynamics simulation and confocal microscopy. The experimental results indicated different amounts of lipids on ethnic hair compositions and higher percentage of hair internal lipids in African hair. In this type of hair, the axial diffraction of keratin was not observed in X-ray analysis, but after hair lipids removal, the keratin returned to its typical packing arrangement. In molecular dynamic simulation lipids were shown to intercalate dimers of keratin, changing its structure. From those results we assume that keratin structure may be influenced by higher concentration of lipids in African hair.